Direktur Perempuan dan Penghindaran Pajak: Apakah Mewujudkan Pengawasan yang Efektif atau Sekadar Simbolisme Tata Kelola? - Indah Kurniyawati; Yanuar Lazuardi; Gilang Dwi Arisandy; Hanna Febrin Utfi Rohmatin (LPPM POLITEKNIK LP3I BANDUNG, 2026)
This study aims to examine the effect of Real Earnings Management (REM) and Accrual Earnings Management (AEM) on tax avoidance and to investigate the moderating role of Women on Board (WoB). Tax avoidance is proxied by Effective Tax Rate (ETR). The study uses data from manufacturing companies listed on the Indonesia Stock Exchange during 2021–2023. By applying a purposive sampling method, this study obtained 380 firm-year observations. Data were analyzed using panel data regression with Stata software. The results indicate that REM and AEM have no significant effect on tax avoidance as proxied by ETR. However, REM has a significant positive effect on BTD, indicating that real activity manipulation may widen the gap between accounting income and taxable income. Furthermore, WoB is not proven to moderate the relationship between earnings management and tax avoidance. These findings suggest that earnings management practices in Indonesian manufacturing companies are more likely used for financial reporting purposes rather than as tax avoidance strategies. This study provides implications for regulators to strengthen supervision over earnings management practices and corporate tax aggressiveness.